The Effect Of Breakfast Habits On The Learning Achievement Of Children In Public Elementary School 2 Tanggungharjo - Wahyu Dewi Hapsari; Sri Martini (Jurnal Profesi Bidan Indonesia, 2022)
Background: Learning achievement is the level of success in a learning process in the form of values. But in reality not all children are able to achieve a good learning achievement because there are many obstacles faced by children. According to data from the Education Office, in 2017 there were 824,635 children who repeated, namely 767,134 children from public schools and 57,501 children from private schools. This can be seen in a preliminary study in 4 elementary schools in the village of Tanggungharjo, Grobogan District, Grobogan Regency. Based on a survey conducted on fourth and fifth grade students in odd semesters at SD Negeri 2 Tanggungharjo, it was found that the average score of students decreased from the previous year. From the results of interviews with some of the children's parents stated that some students rarely have breakfast before doing activities. This is what underlies the researcher to conduct a study entitled the influence of breakfast habits on children's learning achievement at Public Elementary School 2 Tanggungharjo. Purpose: To determine the effect of breakfast habits on children's learning achievement. Method: This type of research is quantitative with a cross sectional research design. The sampling method used is non-probability sampling with a total of 50 respondents. Results: From 50 respondents, most of the children did not eat breakfast (68%) children, and the results of the average value of learning achievement were quite adequate (58%) children. Meanwhile, based on the Chi-Square test, there is an effect of breakfast habits (p = 0.014) on children's learning achievement. Conclusion: Based on the research, it can be concluded that there is a significant influence between breakfast habits on children's learning achievement